2018
DOI: 10.1111/and.13026
|View full text |Cite
|
Sign up to set email alerts
|

Tramadol (opioid) abuse is associated with a dose- and time-dependent poor sperm quality and hyperprolactinaemia in young men

Abstract: Tramadol, one of the most commonly abused drugs in Middle East, impacts spermatogenesis and disturbs reproductive hormones in animal studies. We aimed to investigate tramadol impact on sperm quality and on levels of testosterone, prolactin and gonadotropins, in tramadol abusers (n = 30) to age-matched control (n = 30). Abusers had significantly low percentages of sperm motility, normal forms and vitality compared with control (95% CI -40.7 to -19.3, -13.5 to -9.3 and -31.9 to -9.7 respectively). Hypoandrogenis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 37 publications
2
19
0
1
Order By: Relevance
“…In line with this finding, tramadol has been cited in past studies as a potent drug for its off label effect of increasing intravaginal ejaculatory latency time and for the treatment of premature ejaculation (Abdel‐Hamid et al, ; Kirby, Carson, & Coward, ). While the abuse of tramadol for its off label effect of enhancing sexual performance is widely reported in literature (Abdel‐Hamid et al, ; Kirby et al, ; Wong & Malde, ), a recent study by Farag et al () has also reported low sperm density, motility and vitality among male addicts of tramadol. Future randomized controlled trials would help throw more light on the efficacy and safety of the use of tramadol for it's off label aphrodisiac effect.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this finding, tramadol has been cited in past studies as a potent drug for its off label effect of increasing intravaginal ejaculatory latency time and for the treatment of premature ejaculation (Abdel‐Hamid et al, ; Kirby, Carson, & Coward, ). While the abuse of tramadol for its off label effect of enhancing sexual performance is widely reported in literature (Abdel‐Hamid et al, ; Kirby et al, ; Wong & Malde, ), a recent study by Farag et al () has also reported low sperm density, motility and vitality among male addicts of tramadol. Future randomized controlled trials would help throw more light on the efficacy and safety of the use of tramadol for it's off label aphrodisiac effect.…”
Section: Discussionmentioning
confidence: 99%
“…This reduction may not be sufficient enough to reach a marked statistical significance but it may be of biological significance. Negative feedback effect may also play a role in this effect as indicated by Farag et al [17]. Opioids are well known to affect sexual drive in male humans and rodents [18].…”
Section: Discussionmentioning
confidence: 96%
“…63 Adverse effects of opioids on semen quality have also been described. 64,65 In conclusion, opioid use has inhibitory effect on HPG axis, mainly at hypothalamic level. 28 Dose, type and duration of opioid may play a role on the severity of hypogonadism but further studies are needed to elucidate these.…”
Section: Hypothalamo-pituitary-gonadal Axismentioning
confidence: 87%